Types of social participation and psychological distress in Japanese older adults: A five-year cohort study. - Shiho Amagasa; Noritoshi Fukushima; Hiroyuki Kikuchi; Koichiro Oka; Tomoko Takamiya; Yuko Odagiri; Shigeru Inoue (PLoS ONE, 2017)
INTRODUCTION:The most effective type of social participation against psychological distress in older adults is not well documented. The aim of this study was to examine whether different types of social participation are associated with changes in psychological distress level in older men and women in Japan. METHODS:Two thousand seven hundred community-dwelling older adults (aged 65-74 years, 50% women) were randomly selected from the resident registry of three cities. Of these, participants who reported social participation and psychological distress level in the baseline survey in 2010 were followed up. Psychological distress was evaluated based on K6 scales at baseline and follow-up (in 2015). Social participation level was examined using question items from the National Health and Nutrition Survey in Japan. Exploratory factor analysis was used to derive the underlying factor structure. Multiple linear regression analysis was used to examine the association between social participation and changes in psychological distress level after adjusting for covariates stratified by both gender and age group or living arrangement. RESULTS:Data from 825 community-dwelling older adults (45.3% women) were analyzed. Social participation was categorized into two types using factor analysis: community involvement (volunteer activities, community events, clubs for the elderly) and individual relationship (friendship, communication with family and friends, hobbies). During the 5-year follow-up, 29.5% of participants reported a deterioration in psychological distress. Higher community involvement was independently associated with lower risk of psychological distress for older women (β = 0.099, p = 0.047), whereas there were no associations with individual relationship for either gender. Furthermore, in older women living with others, higher community involvement was also associated with lower risk of psychological distress (β = 0.110, p = 0.048). CONCLUSION:Community involvement provides older women with mental health benefits regardless of individual relationship level. Promoting community involvement may be an effective strategy for healthy mental aging.